Influence of the tense-deformed state on processes of accumulation of tribo damages in barrels of shooter weapon - Писаренко, В.Г. (Problems of Tribology, 2014)
The results of calculation of the tense-deformed state of barrels of sporting and sniper weapon are resulted, ways are indicated for the estimation of accumulation of tribo-damages in.